Spectroscopy of an extreme [O iii] emitting active galactic nucleus at z = 3.212: implications for the reionization era. Issue 2 (12th November 2021) - Tang, Mengtao; Stark, Daniel P; Ellis, Richard S; Charlot, Stéphane; Feltre, Anna; Shapley, Alice E; Endsley, Ryan
ABSTRACT: Reionization-era galaxies often display intense nebular emission lines, both in rest-frame optical ([O iii ] + H β) and ultraviolet (UV; C iii ], C iv ). How such strong nebular emission is powered remains unclear, with both active galactic nuclei (AGNs) and hot stars considered equally viable. The UV continuum slopes of these early systems tend to be very blue (β < −2), reflecting minimal dust obscuration, young ages, and low metallicities. This contrasts with narrow-lined AGNs at z ∼ 2−3, whose UV slopes are significantly redder (β > −1) than typical star-forming systems in the reionization era. To investigate the properties of AGNs in the reionization era, we have conducted a search for potential examples of rare analogues with blue continua at intermediate redshift (z ∼ 2−3). Our goals are to determine whether AGNs with intense line emission and blue continua exist and thereby to establish the range of rest-frame UV and optical line ratios in this population. In this paper, we report the detection of an X-ray luminous AGN at z = 3.21 (UDS-24561) with extreme [O iii ] + H β line emission (equivalent width = 1300 Å) and a blue UV continuum slope (β = −2.34). MMT/Binospec and Keck/MOSFIRE spectra indicate rest-frame UV line ratios consistent with AGN photoionization models and rest-frame optical lines with both a narrow component [full width at half-maximum (FWHM) =154 km s^-1 ] and extended broad wings (FWHM =977 km s^-1 ), consistent with outflowing gas. We describe how such objects can be identified in future James Webb Space Telescope emission line surveys in the reionization era, thereby providing a valuable census of AGN activity at z > 6 and understanding their contribution to cosmic reionization.